Production of glycerol 1,2-carbonate from glycerol with aid of ionic liquid as catalyst - Sairi, Nor Asrina; Ismah, Zati; Alias, Yatimah; Yusoff, Rozita; Taieb Aroua, Mohamed Kheireddine (ECI Digital Archives, 2016)
The surplus formation of glycerol (glycerine or 1,2,3-propanetriol) during biodiesel production has led to a major concern. Glycerol price has dropped and it exerts a great impact on the refined glycerol market. This has triggered an extensive research focus to find an innovative way to revalorize glycerol and transform to value-added chemicals. Yet, it is undeniably a necessary move towards achieving greener and sustainable processes. For instance, glycerol 1,2-carbonate (4-hydroxymethyl-1, 3-dioxolan-2-one) is currently one of the most celebrated glycerol derivatives that captured arising scientific and industrial attentions due to its extensive potential applicability. This cyclic ester of glycerol with carbonic acid is reasonably reactive as it has reactive electrophilic and nucleophilic sites yet having low toxicity and good biodegradability. This important product has attracted numerous applications in chemical industry such as being the novel component of gas-separation membranes, non-volatile solvent for dyes, lacquers, detergents, adhesives and cosmetics, electrolyte ingredient of lithium-based batteries, surfactants and lubricating oils. Likewise, glycerol 1,2-carbonate is beneficial not only as a polar high boiling solvent or intermediate for the synthesis of polycarbonates, polyesters, polyamides and hyper branched polyethers, it also can be used as green substitution for petro-derivatives compounds (ethylene carbonate or propylene carbonate). The reactivity of glycerol 1,2-carbonate having both electrophilic and nucleophilic sites allows for the synthesis of new polymeric materials such as glycidol which is primarily being used in the production of a number of polymers. Please click Additional Files below to see the full abstract.